Studi Kritis Bahan Ajar PAI Materi Mengenal Ketentuan Puasa Sunnah Kelas VI SD Negeri Riunggunung Kabupaten Sukabumi - Nawil Hadad; Siti Qomariyah; Wahid Nurwaluyadin Sofyan; Suhendi Mubarok; Toha Suryana (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This research is based on the importance of relevant and contextual teaching materials that foster understanding and practice of religious values, particularly in the teaching of voluntary fasting at the elementary school level. In the context of Islamic religious education, voluntary fasting material not only aims to provide knowledge but also to shape students' religious character from an early age. The purpose of this study is to critically examine the suitability of the learning objectives, materials, and teaching methods in the teaching materials with the expected competency achievements in the curriculum. The research method used is descriptive qualitative with a document study approach, through content analysis of Islamic Religious Education and Character Education teaching materials for grade VI. Data were collected through documentation techniques and interviews with Islamic Religious Education teachers, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that the teaching materials generally contain voluntary fasting material in accordance with the applicable curriculum. However, there are still shortcomings in aspects of material depth, relevance to students' daily lives, and the diversity of learning methods used. The materials tend to be textual and do not fully encourage students' emotional involvement or spiritual practices. Furthermore, the emphasis on character building and internalization of religious values ​​in students' lives is not optimal. The conclusions of this study indicate the need to develop more applicable, interactive, and contextual teaching materials to improve students' understanding, religious attitudes, and active involvement in consciously and consistently observing the sunnah fast. As a follow-up to these findings, collaboration between teachers, textbook authors, and curriculum developers is crucial to ensure that teaching materials are not only cognitively appropriate.